Hermetia illucens in the Process of Kitchen Waste Biodegradation: The Effect of Different Approaches to Waste Storage on the Microbiological Profile and Nutritional Parameters of the Larvae - Zuzana Mašková; Juraj Medo; Eduard Kolesár; Dana Tančinová; Eva Ivanišová; Dana Urminská; Lukáš Hleba; Jana Urminská; Monika Mrvová; Zuzana Barboráková (Insects)
This study assessed the bioconversion efficiency of Hermetia illucens larvae (BSFL) fed on food waste stored under different conditions, focusing on the nutritional and microbial quality of the resulting larval biomass. Food waste was prepared as a fresh diet (FD) or naturally contaminated and stored at 20–22 °C (OS-T, opened storage-tempered) or under refrigeration, at 5–8 °C (CS-C, closed storage-cooled). Refrigerated, closed storage (CS-C) led to the highest rates of waste reduction (91.0%) and bioconversion efficiency (30.2%), with larvae exhibiting the highest protein content (36.83%) compared to the FD (35.5%) and OS-T (34.71%) groups. Microbiome analysis revealed that the CS-C condition promoted beneficial yeasts like Pichia and Diutia, which correlated positively with improved protein content and microbial safety. In contrast, OS-T storage supported spoilage fungi (Mucor, Rhizopus) and elevated total aerobic counts (7.28 log CFU/g), indicating higher microbial risks. The observed trends in waste reduction and protein content most probably relate to differences in microbial profiles, as controlled cooling affected microbial dynamics, preserving substrate quality and supporting larval growth. These findings emphasize the importance of refrigerated, closed storage to optimize bioconversion, improve larval nutritional value, and minimize microbiological hazards.